2016
DOI: 10.4184/asj.2016.10.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Coronal Proset Magnetic Resonance Imaging to Detect Hidden Zone of the Mid-Zone Stenosis in the Lumbar Spine and Morphometric Analysis of the Mid-Zone Stenosis

Abstract: Study DesignRetrospective exploratory imaging study.PurposeTo investigate the significance of the coronal magnetic resonance imaging (MRI) using Proset technique to detect the hidden zone in patients with mid-zone stenosis by comparing with conventional axial and sagittal MRI and to explore the morphologic characteristic patterns of the mid-zone stenosis.Overview of LiteratureDespite advancements in diagnostic modalities such as computed tomography and MRI, stenotic lesions under the pedicle and pars interarti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Clinically, water excitation techniques have been demonstrated to be useful while examining the musculoskeletal system, in particular, the articular cartilage . More recent publications have shown that the water excitation technique gives better visualization of both normal and pathological nerve roots . This result was particularly true when examining the patient in dorsal plane, allowing a better evaluation of the degree of stenosis and radiculopathy in humans .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, water excitation techniques have been demonstrated to be useful while examining the musculoskeletal system, in particular, the articular cartilage . More recent publications have shown that the water excitation technique gives better visualization of both normal and pathological nerve roots . This result was particularly true when examining the patient in dorsal plane, allowing a better evaluation of the degree of stenosis and radiculopathy in humans .…”
Section: Introductionmentioning
confidence: 99%
“…More recent publications have shown that the water excitation technique gives better visualization of both normal and pathological nerve roots . This result was particularly true when examining the patient in dorsal plane, allowing a better evaluation of the degree of stenosis and radiculopathy in humans . Based on findings in the human literature, our hospital has recently begun using both the dorsal planar STIR and water excitation sequences for cases presenting with an undiagnosed cause for lumbar pain.…”
Section: Introductionmentioning
confidence: 99%